Forming the concept of congruence I. - Szeredi, Éva (Teaching Mathematics and Computer Science, 2011)
Teaching isometries of the plane plays a major role in the formation of the congruence-concept in the Hungarian curricula. In the present paper I investigate the way the isometries of the plane are traditionally introduced in most of the textbooks, especially the influence of the representations on the congruence concept, created in the teaching process. I am going to publish a second part on this topic about a non-traditional approach (Forming the concept of congruence II). The main idea is to introduce the isometries of the two dimensional plane with the help of concrete, enactive experiences in the three dimensional space, using transparent paper as a legitimate enactive tool for building the concept of geometric motion. I will show that this is both in strict analogy with the axioms of 3-dimensional motion and at the same time close to the children’s intuitive concept of congruence.